Psychophysiological correlates between emotional response inhibition and posttraumatic stress symptom clusters - Duan, Hongxia (Sci Rep, 2018)
Post-traumatic Stress Disorder (PTSD) is characterized by diverse executive function impairments as well as abnormal emotion processing. The goal of the present study was to examine the relationships between emotional response inhibition and distinct PTSD symptom clusters from a six-factor DSM-5 model. Event-related potentials (ERPs) were measured in an emotional Go/NoGo task among 58 adult survivors from a deadly earthquake. Overall, the commission errors were lower and reaction time was faster for negative pictures compared to neutral pictures. The negative pictures elicited a smaller N2 but larger P3 amplitude compared to neutral and positive pictures, and larger P3 amplitude was further associated with a faster response. Multivariate regression models showed that the PCL score was related to smaller NoGo-N2 amplitude in the negative context, suggesting that the severity of posttraumatic stress symptoms is associated with worse conflict detection. Furthermore, the severity of anhedonia symptom cluster rather than negative affect symptom cluster was associated with fewer commission errors in the positive context, and this result provided electrophysiological evidence for the six-factor model, i.e., a distinction should be made between negative affect symptom cluster and anhedonia symptom cluster.